IMPLICATIONS OF THE ENACTMENT OF BASIC AGRARIAN LAW ON THE EVIDENTIARY FORCE OF EIGENDOM - Fernando Anggrek; Moh Saleh (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
This study examines the legal implications of the enactment of Law Number 5 of 1960 (UUPA) on the status of colonial-era eigendom rights, specifically concerning land arising from the nationalization of colonial assets transferred to State-Owned Enterprises (SOEs/BUMN). The findings demonstrate that eigendom rights were extinguished upon the enactment of the UUPA and ought to have been converted into the Right to Manage (HPL) or other rights as prescribed by the UUPA. The focus of the study is directed at the conflict in Dukuh Pakis District, Surabaya City, between PT Pertamina (Persero), as the holder of nationalized assets, and community members who have obtained land title certificates. PT Pertamina (Persero)'s claim is founded upon colonial eigendom land rights acquired through the nationalization of Dutch companies. These nationalized assets have not been promptly converted by PT Pertamina (Persero) to date, thereby giving rise to disputes. The arising disputes are primarily attributed to the SOE's negligence in failing to perform the conversion of land rights as mandated by the UUPA. The National Land Agency (BPN), a state institution authorized to issue land title certificates, was also not diligent in tracing the land's provenance when the certificates were issued to the community. Consequently, both the BPN and the SOE failed to regulate and register the nationalized assets, resulting in an overlap between the land's historical status and the rights granted to the community. Therefore, a resolution should be pursued through administrative rectification and state asset verification, while taking into account the circumstances of community members acting in good faith (bona fide) who have acquired their rights through official procedures.